Eye Movement Desensitization Protocol for Urge to Reduce Scratching Behaviour in Patients with Prurigo Nodularis: A Pilot Study - Mathijs R. de Veer; Leonieke W. Kranenburg; Tamar E.C. Nijsten; Jan J. Busschbach; Rick Waalboer-Spuij (Medical Journals Sweden, 2024)
Abstract is missing (Short communication)